Explanatory variables associated with diversity and composition of aquatic macrophytes in a large subtropical river floodplain - Schneider, Berenice (2015)
The structure of aquatic macrophyte assemblages can be affected by myriad factors, including physical, chemical and morphometric characteristics. We describe the patterns of plant species diversity and composition and vegetation height in aquatic ecosystems and their potential determinants at a regional scale in the Middle Paraná River floodplain. Sampling was conducted in twenty-three water bodies, including secondary channels, connected lakes and disconnected lakes. We compared the macrophyte species richness, composition and vegetation height in water bodies with different degrees of connectivity with the river and assessed the most important abiotic explanatory variables (morphometric, physical and chemical) associated with these assemblage attributes. Species accumulation curves showed that species richness did not differ between water bodies with different degrees of connectivity, although it tended to be lowest in secondary channels. Species richness was specifically associated with depth, conductivity, percent of solar radiation reaching the bottom and nitrate. Macrophyte assemblage composition was related primarily to the degree of connectivity, as rare species mostly occurred in disconnected lakes. Composition was also related to the degree of wind exposure (fetch), distance to shoreline and depth. Finally, vegetation height (a surrogate for biomass) was associated with the ammonium and sediment organic matter. Thus, a combination of morphometric and abiotic factors explained species richness, while degree of connectivity and morphometry explained assemblage composition. Vegetation height was explained by nutrients. These results suggest that a single set of variables is not sufficient to explain different aspects of macrophyte assemblages.